laws of logic

You are currently browsing articles tagged laws of logic.

We know that we have distributive rules that handle the disjunction and the conjunction, such as the following

    \begin{align*} p \and (q \orr r) &\Leftrightarrow (p \and q) \orr (p \and r)\\ p \orr (q \and r) &\Leftrightarrow (p \orr q) \and (p \orr r). \end{align*}

But, does there exist a rule, for example, that would handle distributivity of the conjunction with the implication? In other words,

    \[\text{is } p \and (q \rightarrow r) \text{ logically equivalent to } (p \and q) \rightarrow (p \and r)?\]

At least, the above case, the answer is no. We can see this by constructing a truth table like the one below; the truth values of p \and (q \rightarrow r) are not the same as (p \and q) \rightarrow (p \and r).  Hence, p \and (q \rightarrow r) and (p \and q) \rightarrow (p \and r) are not logically equivalent. Therefore, it’s not a rule that we can apply in our proofs.

Rendered by

Tags: , , ,